The Touristudent: How International Academic Mobility Can Contribute to Tourism - Pinto, Mateus José Alves; Moscardi, Eduardo Henrique; Gomes, Ewerton Lemos; Nakatani, Marcia Shizue Massukado (Journal of International Students, 2021)
This research aims to analyze how the activities and motivations of international students resemble those of a tourist. The survey-based study of international students enrolled in academic mobility programs in Curitiba (Brazil) demonstrated that the main motivation for students to participate in international mobility relates more to personal motivation (i.e., cultural exchange) than to academic purposes. International students also acknowledged that they enjoyed the city’s tourist attractions and overall services. The motivations for choosing Curitiba are mainly the quality of life and the perceived safety of the city. Based on how students visit attractions and utilize tourist services, we propose the idea of the touristudent. Understanding international students’ motivations for mobility and their destination choice reinforces the significance that academic mobility programs have for tourism, and the implications of these findings are discussed for the tourism sector in Curitiba.